SOSIALISASI IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI SMP AL FALAH, JATIRAHAYU, PONDOK MELATI, BEKASI - Jatut Yoga Prameswari; Bambang Sumadyo; Dewi Indah Susanti (Lancar Media Komunikasi, 2022)
Literacy is no longer a new thing in our world of education. Where literacy should have become a culture not only for students, but also for educators. Literacy itself is an activity of habitual thinking which is also followed by a reading-writing process and will eventually lead to critical thinking, problem solving, scientific development, and the creation of a work. The school literacy movement (GLS) itself is an implementation of the Minister of Education and Culture Regulation Number 23 of 2015 concerning